Gestión y tratamiento contable de los inventarios de la empresa “Color Market” Cía. Ltda. en el año 2018. - Pardo Sarango, Pardo Sarango (My University, 2020)
The business sector is fundamental for the economy and the competitiveness of nations, for this, an essential element is accounting, through this there is an adequate control of finances, one of the most important items in this regard are inventories This is one of the most complex functions, this is mainly due to the existence of interests and conflicts, the multiple uncertainties that this function entails will depend on each economic sector. Proper order and inventory management are the main factors that influence business performance and therefore the profits of the organization, which is why it is vital to have well-managed and controlled inventories, maintain optimal levels and not generate unnecessary costs, that is why, in order to reduce inventory measurement alternatives, the International Accounting Standards Board has developed the IAS 2 standard, based on the context outlined, the research work proposed was aimed at “ Determine the management and accounting treatment of the inventories of the company Color Market Cía. Ltda. In the year 2018, through an analysis of the International Accounting Standard 2 to know what factors allow to keep an adequate control in the inventories and thus be able to make correct decisions improving the economic stability of the company ”, and as specific objectives“ Evaluate Inventory control management through an analysis of International Accounting Standard 2 of the company Color Market Cía. Ltda. ” and Analyze the control of the accounting treatment that is managed in the inventories of the company Color Market Cía. Ltda. ”, For this purpose, the criteria of different authors have been investigated, in addition to this, the qualitative and quantitative approaches have been considered as a basic research modality, through which it was possible to obtain important conclusions for the Company under study. In order to obtain adequate conclusions that contribute to the improvement of the accounting development of the company, interviews were conducted with the administrator, and with the accounting and warehouse departments, from which it was deduced that the management and accounting treatment of the inventory is not carried out properly In addition to this, the accounting entries were reviewed, in which some problems could be determined, among them the mishandling of purchases and the account of products in process, concluding that the company does not make reports in relation to products that arrive in poor condition, no documents are used for inventory control other than purchase invoices, there is no support for the delivery of materials for production, there is no signature of responsibility in the documents for inventory control, In addition to this, there is no restriction for entering the wineries, so it is recommended that the company train the accounting and accounting staff warehouse so that the accounting management of the inventories is correct, in this way an adequate balance can be established at the end of the fiscal period.
El sector empresarial es fundamental para la economía y la competitividad de las naciones, para esto, un elemento fundamental es la contabilidad, por medio de esta se brinda un adecuado control de las finanzas, uno de los rubros más importantes en este sentido son los inventarios, esta es una de las funciones más complejas, esto se debe principalmente a la existencia de intereses y conflictos, las múltiples incertidumbres que esta función encierra dependerán de cada sector económico. El orden adecuado y la administración de los inventarios son los principales factores que inciden en el desempeño empresarial y por ende en las ganancias de la organización, es por esto que resulta de vital importancia contar con inventarios bien administrado y controlado, mantener niveles óptimos y no generar costos innecesarios, es por esto que, con la finalidad de disminuir las alternativas de medición de inventarios, el Consejo de Normas Internacionales de Contabilidad ha desarrollado la norma NIC 2, en base al contexto planteado, el trabajo de investigación planteado tuvo como objetivo “Determinar la gestión y el tratamiento contable de los inventarios de la empresa Color Market Cía. Ltda. en el año 2018, mediante un análisis de la Norma Internacional de Contabilidad 2 para conocer qué factores permiten llevar un control adecuado en los inventarios y así poder tomar decisiones correctas mejorando la estabilidad económica de la empresa”, y como objetivos específicos “Evaluar la gestión en el control de inventarios mediante un análisis de la Norma Internacional de Contabilidad 2 de la empresa Color Market Cía. Ltda.” y Analizar el control del tratamiento contable que se maneja en los inventarios de la empresa Color Market Cía. Ltda.”, para esto se ha procedido a la investigación del criterio de diferentes autores, además de ello, se ha considerado como modalidad básica de investigación los enfoques cualitativo y cuantitativo, por medio de los cuales fue posible la obtención de conclusiones importantes para la empresa objeto de estudio. Para poder obtener conclusiones adecuadas que aporten a la mejora del desenvolvimiento contable de la empresa, se realizó entrevistas al administrador, y a los departamentos de contabilidad y bodega, de lo cual se dedujo que la gestión y tratamiento contable del inventario no se lleva de manera adecuada, además de esto, se revisó los asientos contables, en los cuales se pudo determinar algunos problemas, entre ellos el mal manejo de las compras y la cuenta de productos en proceso, llegando a la conclusión de que la empresa no realiza informes en relación a productos que llegan en mal estado, no se utilizan documentos para el control de inventarios más que las facturas de compra, no existe un respaldo de la entrega de materiales para la producción, no hay firma de responsabilidad en los documentos para el control de inventarios, además de esto, no existe restricción para el ingreso a las bodegas, por lo cual se recomienda a la empresa capacitar al personal de contabilidad y de bodega para que el manejo contable de los inventarios sea el correcto, de esta manera se podrá establecer un balance adecuado al finalizar el periodo fiscal.
Keywords: COMPETITIVIDAD; INVENTARIO; BALANCE; ECONOMÍA